Inflammatory-based prognostic indicators in prostate cancer: evaluating NLR, PLR, and SII in relation to Cambridge and ISUP classifications - Patrzałek, Patryk; Froń, Anita; Mielczarek, Maja; Karwacki, Jakub; Lesiuk, Grzegorz; Janczak, Dawid; Nagi, Krystian; Krajewski, Wojciech; Dębiński, Paweł; Szydełko, Tomasz; Małkiewicz, Bartosz (Frontiers in Oncology, 2025)
IntroductionSystemic inflammation is increasingly recognized for its role in cancer prognosis. Inflammatory markers such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic inflammation index (SII) are emerging as relevant factors in oncology. This study evaluates their associations with established prognostic classifications in prostate cancer (PCa): the Cambridge Prognostic Groups (CPG) and the International Society of Urological Pathology (ISUP) grading system.MethodsA retrospective cohort study was conducted on 272 prostate cancer patients using systematically collected clinical data. We calculated and analyzed NLR, PLR, and SII concerning CPG and ISUP scores.ResultsStatistically significant relationships were found between NLR, SII, and prognostic classifications. PLR did not demonstrate any significant association.ConclusionNLR and SII may be helpful to prognostic factors in PCa, particularly in outpatient settings. However, further multi-center validation and establishing standardized cut-off values are necessary.